HUBUNGAN INDEKS PEMBANGUNAN MANUSIA DENGAN INDIKATOR PENYAKIT, LINGKUNGAN, DAN GIZI MASYARAKAT (Analisis Data Sekunder Negara Anggota UNDP) - Andrei Ramani (Jurnal Ilmu Kesehatan Masyarakat, 2014)
Background: Human Development Index (HDI) is a composite index that calculated based on life expectancy, education level, and income. HDI is one of indicators to measure the development of specific region and one single statistics indicator that served as a social and economic development reference. Objective: Objectives of this research is to looking at correlative phenomena between HDI and the percentage of cases, rate/ratio, or any other similar indexes in certain area such as: disease, environment, and community nutrition in international level. Method: The research method is Cross - National study by using the country as the unit analysis and looking at the country as part of international ecosystem components that can be compared. Selected countries are the member of UNDP as many as 187 countries. Result: The results showed a statistically significant relationship between HDI, EPI, GHE, mortality rate of the disease (infectious and non-infectious disease), and the percentage of malnutrition and overweight in children (under 5 years). Keyword: HDI, EPI, GHE, mortality, malnutrition, overweight